Role of Carrot (Daucus carota L.) Storage Roots in Drought Stress Adaptation: Hormonal Regulation and Metabolite Accumulation - Kyoung Rok Geem; Ye-Jin Lee; Jeongmin Lee; Dain Hong; Ga-Eun Kim; Jwakyung Sung (Metabolites)
Background: Drought stress has become one of the biggest concerns in threating the growth and yield of carrots (Daucus carota L.). Recent studies have shed light on the physiological and molecular metabolisms in response to drought in the carrot plant; however, tissue-specific responses and regulations are still not fully understood. Methods: To answer this curiosity, this study investigated the interplay among carrot tissues, such as leaves (L); storage roots (SRs); and lateral roots (LRs) under drought conditions. This study revealed that the SRs played a crucial role in an early perception by upregulating key genes, including DcNCED3 (ABA biosynthesis) and DcYUCCA6 (auxin biosynthesis). The abundance of osmolytes (proline; GABA) and carbohydrates (sucrose; glucose; fructose; mannitol; and inositol) was also significantly increased in each tissue. In particular, LRs accumulated high levels of these metabolites and promoted growth under drought conditions. Conclusions: Our findings suggest that the SR acts as a central regulator in the drought response of carrots by synthesizing ABA and auxin, which modulate the accumulation of metabolites and growth of LRs. This study provides new insights into the mechanisms of tissue-specific carrot responses to drought tolerance, emphasizing that the SR plays a key role in improving drought resistance.